Novel Selection Marker for Mammalian Cell Transfection - Raymond P. Baumann; David H. Sherman; Alan C. Sartorelli (BioTechniques)
The availability of selectable markers suitable for use in mammalian cells has permitted the analysis of the influence of the stable overexpression of single or multiple genes on specific cell properties. This powerful technique has led directly to many fundamental advances in molecular biology and increased our overall understanding of cell growth and regulatory events. Although a variety of selectable markers are currently available, some cell lines continue to be naturally resistant to certain markers, making direct selection difficult or not feasible. Thus, the characterization of additional cell selectable markers continues to be of interest. We have developed a novel selectable marker based on mitomycin C resistance that is suitable for stable transfection of mammalian cells. This system is based on the ability of the mcrA gene, isolated from Streptomyces lavendulae, to confer mitomycin C resistance to both bacterial and mammalian cells by expression of the MCRA protein. Here we demonstrate that mcrA can be used as a selectable gene marker in Chinese hamster ovary cells when cells transfected with the mcrA gene are either pulsed or cultured continuously with mitomycin C. This unique selection system may be of use for transfection of cells that are resistant to currently available selectable markers.